Knee surgery tricks of the trade - Stannard, James P.; Schmidt, Andrew; Kfuri, Mauricio (Thieme, 2022)
An indispensable step-by-step guide on a full spectrum of open and arthroscopic knee procedures Knee disorders are among the most common musculoskeletal conditions and, as such, constitute four of the top seven orthopaedic procedures. Currently, 720,000 knee replacements are performed annually in the US, with a projected 3.4 million surgeries by 2030. Knee Surgery: Tricks of the Trade edited by renowned knee surgeons and educators James P. Stannard, Andrew Schmidt, and Mauricio Kfuri features contributions from an impressive cadre of distinguished colleagues. The reader-friendly book fills a g